Comparison of changes in starch contents in the cotyledons of Radish and Lablab - K. Sharma, Shweta Tiwari; Dr. (International Multidisciplinary Research Journal, 2011)
The major storage materials of the seeds are carbohydrates, mostly starch, protein and lipids. There occurs a great difference among the seeds in their reserve composition. Starch is the major stored reserve in both Radish and Lablab cotyledons. Most of such work is done in cereal grains might be due to advantages inherent with cereals which ensure easy manipulation of the system. However the work done so far with facts does open up some interesting possibilities of regulation of stored resources. Since the sugar level is low in the quiescent seeds in the phase of radical emergence between 24 to 48 hrs the starch degradation is negligible. The rate of degradation is found to be 24% and 22% for Radish and Lablab respectively.